Implementasi Metode Profile Matching dan Multi Factor Evaluation Process (MFEP) Dalam Seleksi Pencari Kerja - Heru Purwanto; Arfhan Prasetyo; Rachmat Suryadithya (LPPM Universitas Bina Sarana Informatika, 2021)
An effective job seekers selection process at the company is needed to assist an organization's decision making. The purpose of this paper is to create a system and development of a decision-making system in the human resources (HR) section to find it easier to determine whether job seekers are accepted or not. The multi factor evaluation process (MFEP) is a very effective approach in dealing with decision problems and Profile matching is a multi-criteria selection method, where the determination of aspects and criteria (name of school, appropriate department, GPA value meets, year of graduation, relevant courses, work experience in the appropriate field, projects that have been handled, salary suitability, domicile, honest, responsible and discipline, cooperation, communicative and self-confidence). The advantage of the profile matching method is the provision of standard values from the main and supporting criteria, making it easier for system users to determine the available options. MPEF needs to define the education value factor, target value and attitude value. The final calculation results provide information referring to the same name. Profile Matching method in the first order with a value of 4.62, the second order of 4.59 and the third order of 4.52. The first order MFEP method = 0.513, the second order = 0.510 and the third order = 0.502. This decision support system not only makes it easier to determine the assessment of job seekers but also provides an alternative sequence of candidates who have the potential to be considered by companies or organizations